Human Resource: To Evaluate the Performance Appraisal Mechanism; Perspective of the Employees ((PJHAS) PUSA Journal of Hospitality and Applied Sciences, 2025)
Background: This study evaluates the effectiveness and perception of the performance appraisal mechanism from the  employees’ perspective. Objective: To evaluate the performance appraisal mechanism and understand its impact on  employee motivation, perception and productivity. Methodology: A quantitative survey-based approach was adopted  among 100 employees working across hospitality, education, marketing, and IT organizations in Delhi and NCR. Data  were collected through a structured questionnaire and analyzed using descriptive statistics. Results: The findings  reveal that a majority of employees consider appraisals an important driver of motivation and fairness. Constructive  feedback and transparent communication were identified as crucial determinants of satisfaction. Conclusion: The study  concludes that fair and well-communicated appraisal systems improve employee engagement, trust and organizational  performance.
Keywords: Performance appraisal; employee motivation; fairness; feedback; organizational performance